2004
DOI: 10.1049/ip-com:20040662
|View full text |Cite
|
Sign up to set email alerts
|

Improving fairness in IEEE 802.11 using enhanced carrier sensing

Abstract: Fair access of the shared wireless medium among different contending stations is a very important issue, especially when quality of service needs to be provided. In the CSMA/CA-based IEEE 802.11 protocol, carrier sensing (CS), collision avoidance (CA) and contention resolution (CR), the three main components, affect its fairness. While the influences of CA and CR on the fairness have already been documented, to the best of the authors knowledge there is no research work taking into account CS's influence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Many studies have been undertaken, in different research fields, to explicitly examine the relationship between the MAC and the PHY layers. Results from these studies [28], [29], [30], [31], [32] highlight the importance of considering the impact of the PHY on the MAC, thus, provide motivation for performing such an investigation in adaptive PCS.…”
Section: On Physical Carrier Sensing In Wireless Ad-hoc Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been undertaken, in different research fields, to explicitly examine the relationship between the MAC and the PHY layers. Results from these studies [28], [29], [30], [31], [32] highlight the importance of considering the impact of the PHY on the MAC, thus, provide motivation for performing such an investigation in adaptive PCS.…”
Section: On Physical Carrier Sensing In Wireless Ad-hoc Networkmentioning
confidence: 99%
“…Consequently, hidden nodes are particularly prevalent in IEEE802.11 wireless ad-hoc networks and WMNs. Moreover, a significant number of studies have shown that VCS is fundamentally limited in mitigating hidden node interference in these architectures [13], [14], [28], [38]. This section describes current adaptive carrier sensing mechanisms and protocols, designed to overcome the deficiencies of the CSMA/CA algorithm in wireless ad-hoc networks.…”
Section: Adaptive Physical Carrier Sensing In Ieee 80211 Wirelessmentioning
confidence: 99%
“…The carrier sensing mechanism for the MAC layer behaved as if the minimum reception threshold was not modified. If the carrier sensing mechanism were changed, the collision avoidance attributes, spatial reuse [29][30][31] and medium access [32] would be affected. Table 5.…”
Section: Simulation Environmentmentioning
confidence: 99%
“…It is worth noting that throughput of 802.11 networks may be enhanced by attending to many different aspects of the 802.11 MAC protocol; this is the subject of extensive work, such as [7] [8] [12] to cite a few. Hence maximizing network performance must be a careful combination of approaches addressing multiple aspects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This has it's limitations; the overhead due to the additional RTS/CTS handshake is not justified when the data payload size is small. More significantly, it has been shown that virtual carrier sensing has fundamental limitations in avoiding interference from hidden terminals in mesh networks [7] [10] [11] [12], i.e. there are many scenarios where it is conservative and fails to suppress packet collisions as intended.…”
Section: Introductionmentioning
confidence: 99%